Mass cytometry of platelet-rich plasma: a new approach to analyze platelet surface expression and reactivity. (18th August 2022) - Klug, Melissa; Kirmes, Kilian; Han, Jiaying; Lazareva, Olga; Rosenbaum, Marc; Viggiani, Giacomo; von Scheidt, Moritz; Ruland, Jürgen; Baumbach, Jan; Condorelli, Gianluigi; Laugwitz, Karl-Ludwig; List, Markus; et al.
Abstract: Mass cytometry (CyTOF) is a new technology that allows the investigation of protein expression at single cell level with high resolution. While several protocols are available to investigate leukocyte expression, platelet staining and analysis with CyTOF have been described only from whole blood. Moreover, available protocols do not allow sample storage but require fresh samples to be obtained, processed, and measured immediately. We provide a structured and reproducible method to stain platelets from platelet-rich plasma to study thrombocyte protein expression and reactivity using mass cytometry. With our method, it is possible to acquire a large number of events allowing deep bioinformatic investigation of platelet expression heterogeneity. Integrated in our protocol is also a previously established freezing protocol that allows the storage of stained samples and to delay their measurement. Finally, we provide a structured workflow using different platelet stimulators and a freely available bioinformatic pipeline to analyze platelet expression. Our protocol unlocks the potential of CyTOF analysis for studying platelet biology in health and disease.